The influence of exfoliated graphite on sensing properties of chitosan / PVA based ammonia sensors - Nur Zuraihan Abd Wahab (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The research objectives are to investigate the effect of exfoliated graphite on microstructure, electrical conductivity and band gap of chitosan/polyvinyl alcohol films ; to analyze the effect of electrochemical deposition voltage and deposition time on the sensing properties of chitosan/polyvinyl alcohol/exfoliated graphite film sensors ; to investigate the effect of exfoliated graphite on sensing properties of chitosan/polyvinyl alcohol film sensors toward ammonia.